Data Acquisition System on Cocoa Bean Fermenter Using ESP32 Based on MQQT Protocol - Akbar, Zainal; Yuriadi; Sidehabi, Sitti Wetenriajeng (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2024)
The fermentation process of cocoa beans is a critical stage in chocolate production that affects the final quality of the product. To ensure that fermentation takes place optimally, monitoring parameters such as temperature, humidity, and pH is necessary. This research aims to develop and validate an Internet of Things (IoT)-based data acquisition system that uses ESP32 and MQTT protocols to monitor the fermentation process of cocoa beans. The system consists of an ESP32 module connected to DHT22 sensors to measure temperature and humidity, and a pH meter to measure acidity. The data collected by the sensors is sent in real-time via a wireless connection to an MQTT broker, where it can be monitored continuously. System testing was conducted in a small-scale fermentation environment. Validation results show that the system is capable of providing accurate and consistent data when compared to manual measurements using standardized tools. The difference between the data collected by the system and manual measurements was within acceptable tolerance limits, indicating that the system is reliable enough to be used in small-scale applications. The system also demonstrated fast response to changes in fermentation conditions, and stable data connection with minimal latency via the MQTT protocol. The developed data acquisition system has successfully acquired data and validated it using standard measuring instruments. The average data error for the pH sensor is 2.78%, temperature sensor 1.41%, and humidity sensor 1.94%. These error values indicate that the performance of the sensors used is good.